Methods for creating bare ground on farmland in Hampshire, UK, and their effectiveness at recruiting ground-nesting solitary bees - Nichols, R N; Holland, J; Goulson, D (Conservation evidence, 2020)
Solitary bees have experienced a decline in both diversity and abundance over the past decade. Although their foraging requirements have been the subject of some recent studies, their nesting requirements have received little attention. Some species of ground-nesting solitary bees have shown an affinity for hard, bare ground as preferred locations for nests. Here we assessed two different methods for creating bare ground plots on farmland and observed the different rates at which these plots recruited ground-nesting bees. Three approximately 6 m2 plots were created at each of 19 locations. One was scraped bare using machinery, a second was sprayed-off with herbicide, and the third was left undisturbed as a control plot. The results showed a significantly greater number of nests in the scraped plots compared to the sprayed or control plots, with the majority of these nests being created in April. This trial shows that an agri-environment scheme could be effective to support the creation of nesting areas for solitary bees on farmland.